Huck. Book 1, All-American - Millar, Mark; Millar, Mark; Albuquerque, Rafael, 1981- (Image Comics, 2016)
"In a quiet seaside town, a gas station clerk named Huck secretly uses his special gifts to do a good deed each day. When his story leaks, a media firestorm erupts, bringing him uninvited fame. As pieces of Huck's past begin to resurface, it's no longer clear who his friends are -- or whose lives may be in danger."--Provided by publisher.